Гарем: [роман] : (18+) / Бертрис Смолл ; [перевод с английского В. Ю. Смирнова] - Смолл Бертрис (АСТ, 2015)
Экземпляры: ф.22 (20151221) / Инвентарный номер: 060079 / Цена: 251.00 / Авт.знак: С 51 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)